Thermomechanically induced phase separation at elevated temperatures in a CoCr0.4NiSi0.3 medium-entropy alloy - Li Zhang; Lijia Chen; Weiqiang Zhang; Hui Zhao; Feng Li (Journal of Materials Research and Technology)
The microstructural evolution of an as-cast CoCr0.4NiSi0.3 medium-entropy alloys (MEA) was investigated under quasi-static tensile tests from 200 °C to 800 °C. The face-centered cubic (FCC) matrix exhibited ordered nano-precipitates induced by phase separation, resulting in varying strengthening mechanisms caused by metastable phase separation at elevated temperatures. The directional vacancy diffusion of solute atoms along specific crystal planes of dynamically recrystallized (DRXed) grains leads to phase separation at elevated temperatures. This occurs through pathways along the crystal planes of {02‾1‾} in the DRXed σ phase at 400 °C and the {055‾0} in the secondary α-M5Si3 phase at 800 °C. The diffusion mechanism involves lattice defects at lower temperatures and lattice interdiffusion at elevated temperatures. Additionally, the FCC-structured MEA enhances strength and plasticity through the TRIP effect by decomposing perfect dislocations to form the 9R phase. The interaction mode between the primary precipitated L12 phase and dislocations varies with temperature. At 400 °C, a/3<112> dislocation pairs cut through the L12 phase, while at 800 °C, an Orowan mechanism bypasses the L12 phase. The favorable mechanical properties of the as-cast MEA at elevated temperatures can be attributed to the temperature-dependent evolution of metastable phase configurations and their interactions with dislocations during thermomechanically tensile testing, providing insights into the evolution of metastable phases in CoCrNi-based MEAs under elevated temperatures.